CORRUPTION PREVENTION STRATEGIES THROUGH IMPROVING THE QUALITY OF FINANCIAL REPORTS AND STRENGTHENING HUMAN RESOURCES IN LOCAL GOVERNMENTS IN INDONESIA - Gracia Carolina Yusuf; Muhammad Din; Jurana; Andi Chairil Furqan (Universitas La Tansa Mashiro, 2025)
This study aims to analyze the effect of the quality of financial reports and strengthening human resources on corruption prevention strategies in local governments in Indonesia. The approach used is quantitative with secondary data obtained from the Overview of Audit Results of the Supreme Audit Agency, the Central Bureau of Statistics, and the Performance Report of the Financial and Development Supervisory Agency. The data covers the period 2021-2023, with a total of 1,590 observations from 542 local government entities. Data analysis was carried out using the SEM PLS method using WarpPLS 8.0. The results of this study indicate that both variables, the quality of financial reports and strengthening human resources, have a significant positive relationship with the effectiveness of corruption prevention strategies. Transparently prepared financial reports not only strengthen public trust, but also become an instrument of supervision in detecting and preventing potential irregularities. On the other hand, superior human resources in terms of education, ethics, and understanding of the internal control system also strengthen the implementation of anti-corruption policies in the field.